Gender Performance in Party Brief Success - Shane A. Gleason; Jennifer J. Jones; Jessica Rae McBean (Washington University Journal of Law & Policy, 2017)
This Article evaluates the success of female attorneys before the Supreme Court as a function of conforming to gender expectations. Gleason, Jones, and McBean reject the traditional gender male-female dichotomy in favor of an evaluation based on gender as performance and the social norms expected from each gender. The authors hypothesize that those female lawyers who appear before the Supreme Court find more success when they express female gender norms in their communications as opposed to embracing the traditional male styles that already permeate the legal field. The Article concludes that there is some correlation between female success before the court and when gender norms are followed, and suggests that further work is needed in the area at various court levels.
Keywords: Gender; Norms; Party Brief; Supreme Court; Study